Primary Student Teachers’ Views on Scientific Measurement and Uncertainty: A Pilot Research - Georgaki, Maria; Stefanidou, Constantina (Advances in Social Sciences Research Journal, 2023)
The paper presents primary student teachers’ views on the basic concepts related to scientific measurement and uncertainty. A pilot study was conducted, and a qualitative content analysis method was used, by distributing an open-ended questionnaire in a convenient sample including 24 primary student teachers. The first findings revealed that student teachers have some general idea about the importance of scientific measurement, they recognize uncertainty as human error or instrument failure, but they lack the deepest conceptualization of uncertainty as an aspect of the nature of scientific measurement. The above-mentioned views are discussed in the context of their influence in teaching practices of science and mathematics in primary education and their epistemological perspectives.